OVERVIEW OF STROKE INCIDENCE IN THE WORK AREA OF PUSKESMAS KAWAL - Romalina Romalina; Asmarita Jasda; Meisa Daniati; Yas Suriani; Widia Jannatul Amani; Adila Hidayati (International Journal of Social Science, 2022)
Stroke is a disease that attacks a person suddenly and it is one of the leading causes of death and neurological disability in Indonesia except heart disease and cancer. Various conditions related to the increase in the incidence of stroke. The purpose of this study is to determine the picture of stroke incidence in the work area of the Kawal Health Center in 2019. The source of data from this study is a secondary data source, namely patient medical records at the Kawal Health Center from October 2018 to April 2019. The data source is then processed and made a frequency distribution. The results showed that the incidence of stroke in 2019 was 9 events. Other supporting conditions are the discovery of stroke risk factors, including Hypertension as many as 41 people (77%), Diabetes Mellitus 12 people (23%) for 2018. Meanwhile, in 2019, data on hypertension risk factors were obtained by 196 people (85%) and risk factors for Diabetes Mellitus 34 people (15%). It is hoped that the puskesmas can provide counseling to the community about the emergency of stroke